THE IMPLEMENTATION OF DICTOGLOSS STORYTELLING IN IMPROVING 8th GRADE STUDENTS’ WRITING ABILITY - Azharra Aninda Putri Al Farid; Sri Setyarini; Nicke Yunita Moecharam (Journal of English and Education, 2017)
This study investigates the implementation of Dictogloss Storytelling in 8th grade english classroom. It aims to see its contribution to the improvement of students’ writing performance in writing narrative texts. The study used experimental study as quantitative strand. It involved a class consisting of 19 students as the experimental group. The data were obtained from three meetings of teaching program.Hypothesis testing revealed that the post-test score (M = 64.00 , SD = 10.41) was significantly higher than pre-test score (M = 52.95, SD = 8.47), in t(18) = -10.849, p .05, r2 = .867 in 2-tailed direction. The effect size was also considered as large (r2.25), which indicated that the intervention had a large impact to the students’ score. The extent to which the students had significant improvement in their narrative writing is further explored.